Tetrac and NDAT Induce Anti-proliferation via Integrin αvβ3 in Colorectal Cancers With Different K-RAS Status - Chin, Yu-Tang; He, Zong-Rong; Chen, Chi-Long; Chu, Hsiao-Ching; Ho, Yih; Su, Po-Yu; Yang, Yu-Chen S. H.; Wang, Kuan; Shih, Ya-Jung; Chen, Yi-Ru; Pedersen, Jens Z.; Incerpi, Sandra; et al. (Frontiers in Endocrinology, 2019)
Colorectal cancer is a serious medical problem in Taiwan. New, effective therapeutic approaches are needed. The selection of promising anticancer drugs and the transition from pre-clinical investigations to clinical trials are often challenging. The deaminated thyroid hormone analog (tetraiodothyroaceti acid, tetrac) and its nanoparticulate analog (NDAT) has been shown to have anti-proliferative activity in vitro and in xenograft model of different neoplasms, including colorectal cancers. However, mechanisms involved in tetrac- and NDAT-induced anti-proliferation in colorectal cancers are incompletely understood. We have investigated possible mechanisms of tetrac and NDAT action in colorectal cancer cells, using a perfusion bellows cell culture system which allows efficient, large-scale screening for mechanisms of drug actions on tumor cells. Although integrin αvβ3 in KRAS wild type colorectal cancer HT-29 cells was far less than that in KRAS mutant HCT116 cells, HT29 was more sensitive to both tetrac and NDAT. Results also indicate that both tetrac and NDAT bind to tumor cell surface integrin αvβ3, the agents may have different mechanisms of anti-proliferation in colorectal cancer cells. K-RAS status appears to play an important role in drug resistance that may be encountered in treatment with this drug combination.